Enantioseparation of basic drugs by reverse phase high‐performance liquid chromatography system using carboxymethyl‐β‐cyclodextrin as chiral mobile phase additive. Issue 8 (16th May 2022) - Ao, Qiong; Zhao, Hongliang; Tong, Tianzhong; Peng, Yangfeng; He, Zhaoyang
Abstract: A rapid and efficient method was developed for enantioseparation of basic drugs, using carboxymethyl‐β‐cyclodextrin (CM‐β‐CD) as chiral mobile phase additive, rather than involving costly chiral column in high‐performance liquid chromatography (HPLC) system. Four of the six basic drug enantiomers investigated were successfully separated. The highest resolution reaches 2.15 for threo‐(1S, 2S)‐2‐amino‐l‐p‐nitrophenyl‐1, 3‐propanediol. The effects of the organic modifier, pH value, concentration of chiral additive, column temperature, and flow rate of mobile phase on the enantioseparation of analytes were researched. The apparent formation constants of inclusion and the thermodynamic parameters were evaluated to explain the mechanism of chiral recognition. Abstract :